1985
DOI: 10.1159/000206175
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Iron, Vitamin B<sub>12</sub>, Folic Acid and Their Binding Proteins during Pregnancy

Abstract: One hundred pregnant women, not anemic and not receiving iron or vitamin supplements, were chosen at random among the three trimesters of pregnancy to determine the incidence of unexpected iron, plasma folate and/or cobalamin deficiency, and the significance of fluctuating levels of their respective binding proteins. Pregnant females had a nonsignificant fall in serum iron and a fourfold decline in serum ferritin in the 3rd trimester compared with 1st trimester values. There was a steady decrease in plasma cob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
2

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 11 publications
1
5
0
2
Order By: Relevance
“…The falsely low B 12 may be the result of the low TCI levels found in 60% of this cohort. A similar finding is noted in normal pregnancy, with steadily decreasing B 12 levels throughout the three trimesters, correlating with a decrease in TCI levels over the same period [22]. As TCI is basically produced by granulocytes, it seems that OCs may exert some inhibitory effect on these cells, although 40% of the women had normal TCI levels and therefore, another metabolic pathway may be the cause for low vitamin B 12 .…”
Section: Discussionsupporting
confidence: 67%
“…The falsely low B 12 may be the result of the low TCI levels found in 60% of this cohort. A similar finding is noted in normal pregnancy, with steadily decreasing B 12 levels throughout the three trimesters, correlating with a decrease in TCI levels over the same period [22]. As TCI is basically produced by granulocytes, it seems that OCs may exert some inhibitory effect on these cells, although 40% of the women had normal TCI levels and therefore, another metabolic pathway may be the cause for low vitamin B 12 .…”
Section: Discussionsupporting
confidence: 67%
“…(Rothenberg et al, 1974;Sauberlich, 1975). However, as noted previously by Matte et al (1984) Wagner, 1985;Zamorano et al, 1985). In pigs, Mantzos et al (1974) noted the presence of a great quantity of unsaturated &dquo;avid specific binders&dquo; of folic acid in blood plasma of animals between 2 days and 3 years of age.…”
mentioning
confidence: 55%
“…However, when data are analyzed by trimester of pregnancy, it can be observed that during the first trimester there is a 44.79% deficiency, which is not explainable by a dilution effect, but also is too high to be only due to a nutritional deficiency. Trying to explain the high prevalence of vitamin B 12 deficiency during pregnancy besides the dilution effect, some authors have proposed changes in nutrient transference to the fetus, increased requirement and impaired absorption, especially in underdeveloped countries (Zamorano et al, 1985;Knight et al, 1994;Allen et al, 1995;Mc Grath et al, 1995;O'Connor 1995;Casterline et al, 1997).…”
Section: Discussionmentioning
confidence: 99%